Policy and Physical Activity Programs: Understanding the Lived Experiences of Fathers in Vancouver's Downtown Eastside - Webb, Jessica (Université d'Ottawa / University of Ottawa, 2021)
The role of fatherhood in communities that experience marginalization is not well understood in academic literature. Further, there is little known about the implementation and evaluation of physical activity programs that are accessible and suitable for fathers who experience income instability, racial discrimination, precarious housing, gender discrimination, and domestic and/or sexualized violence. In this thesis, which is presented in the publishable paper format and is comprised of two papers, I sought to address these gaps. Informed by a constructionist epistemology and an intersectional poststructuralist theoretical framework, in the first paper, I used document analysis and Bacchi and Goodwin’s (2016) “What’s the problem represented to be approach” to investigate how fathers are represented in the program policies of organizations that provide family-centred services in the Downtown Eastside of Vancouver, British Columbia, Canada. In the second paper, guided by the methodological tenets of community-based participatory research, I used semi-structured interviews and critical discourse analysis to better understand how men’s lived experiences as fathers in the Downtown Eastside shaped their participation in Make a Move: Family Walking Program. Taken together, the findings from both papers provide insight into the lived experiences of fathers and the roles that policy and physical activity play in shaping fatherhood in the Downtown Eastside.
Keywords: Fathers; Fatherhood